Philippines Quarterly Update, June 2010 : The Recovery Continues Despite Global Financial Turbulence - World Bank (Washington, DC, 2017)
The Philippines economy posted robust growth in early 2010, in part due to large one-off factors. As did many countries in the region, the Philippines benefited from a strong rebound in global trade. Manufacturing and investment activity expanded briskly as a result. Private consumption continued to expand, as consumer confidence improved. Growth also benefited from election-related spending. Expansionary (and now pro-cyclical) fiscal policy continued to support growth. Despite a withdrawal of liquidity-enhancing measures and a stronger peso, a closing output gap meant that monetary policy remained accommodative. A World Bank study of Philippines migration pattern during the global recession reveals that deployment of overseas foreign workers (OFWs) actually accelerated during the crisis. Partly this reflected the fact that the top OFW destinations were not as affected as the rest of the world. The most affected OFWs were males, production workers (especially construction workers) and new hires. By contrast, females, services workers, seafarers and rehires proved resilient to the crisis or even benefited from it. Globally, less tolerance towards weak public finances is expected, raising the need to introduce a credible medium-term fiscal consolidation plan for the Philippines. Running a pro-cyclical fiscal policy with relatively high debt and limited fiscal space-as undertaken in the first-half of 2010-raises risks and should be reverted. Credibility towards such a goal could be achieved, for example, by designing a comprehensive multi-year reform package. As the output gap closes, the accommodative monetary policy introduced in 2008 would need to be gradually unwound, starting by reaching a broadly neutral stance in 2010. An increase in policy rates currently negative or slightly positive could achieve such a goal.